Analysis of Increasing Physical Fitness Through Physical Education after the Covid-19 Pandemic - Jamhari; Trias Ramadhan; I Made Dwi Sastra Wargama (UNIB Press, 2023)
Problems regarding physical fitness when allowed to return to activities outside the home after the implementation of work from home during the Covid-19 pandemic need attention for teachers at schools. The subject closest to fitness is physical education, bearing in mind that in physical education movement activity, movement quality, and movement skills are learning objectives that must be achieved. This research will provide an overview of the literature regarding how physical education can improve student fitness which is expected to lead to healthy and achieving students. This study uses a combination of interactive qualitative and non-interactive qualitative methods. The non-interactive qualitative method in this research is in the form of a literature review model or literature study. While the interactive qualitative method is in the form of interviews with students. The results of literature studies based on research published nationally and internationally show that fitness can be improved through correct movement habits. Movement habits at school can only be obtained by following physical education subjects. So that physical education can improve the fitness of students with motion activities. The motion in question is not just moving but improving the quality of the motion. Because with the increase in the quality of movement, the quality of life also increases. Interactive qualitative results are in line with literacy in which students feel an increase in fitness marked by the ability of students to carry out activities without feeling tired which means after the implementation of Physical Education at school. As a follow-up to this research, it is hoped that research related to increasing fitness through physical education will examine more about innovation in methods, models and strategies for learning physical education so that the physical education carried out is of good quality and even better.